(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Acute caffeine exposure had been shown to induce hyperglycemia however; the influence of thyroid hormones on the caffeine-induced hyperglycemia is yet to be established. The present study was therefore designed to investigate the effect of caffeine exposure on blood glucose and hepatic glycogen content in thyroidectomized rats. Sixty adult male Wistar rats were randomly divided into 10 groups as I-X (n=6). Rats in groups I, III, V, VII and IX were given normal saline, caffeine, prazosin + caffeine, propranolol +caffeine, combined prazosin+ propranolol+caffeine injections respectively while rats in groups II, IV, VI, VIII and X were thyroidectomized and treated in similar manner as the normal rats respectively. Surgical removal of the thyroid gland was done in the thyroidectomised groups while sham-operation was done in Normal group to serve as control. After healing and following an overnight fast, the rats were anaesthetized and the femoral vein and carotid artery were cannulated for drug administration and blood glucose measurement respectively. After stabilization, following basal measurements, rats from each group were injected normal saline or caffeine (6mg/kg) while another sets were pre-treated prazosin (0.2 mg/kg), propanolol (0.5 mg/kg) or their combination before caffeine administration. Blood glucose was then monitored for 60 minutes post-injection of caffeine at 5 minutes interval. Liver samples were collected at the end of the observation period for glycogen content determination. Caffeine caused significant increased blood glucose levels in both normal and thyroidectomized rats which were up to 210% and 180% respectively at the peak of their responses. Liver glycogen content of the thyroidectomized rats (3.11 ± 0.20 mg/100g tissue weight) was significantly higher than the normal rats (1.91 ± 0.43 mg/100g tissue weight). These glycogen contents were significantly reduced by caffeine in both normal (0.25 ± 0.04 mg/100g tissue weight) and thyroidectomized rats (1.65 ± 0.16 mg/100g tissue weight) when compared with their controls. The caffeine effects on blood glucose and hepatic glycogen content were abolished by pretreatment with propanolol or a combination of prazosin and propanolol in both normal and thyroidectomized rats but pretreatment with prazosin caused only significant reduction in hyperglycemic response to caffeine. The findings of this study suggest that caffeine-induced hyperglycemia in both normal and thyroidectomized rats are mediated through both alpha and beta adrenoceptors